Knowledge Management and IT Project Success: A Meta-analytic Review - Chong, Josephine; Teo, Stephen; Leong, Paul; Tan, Felix (ACIS, 2014)
There are fragmented and contradictory findings in relation to the factors influencing IT project success. The aim of this study is to examine the antecedents of IT project success. A meta-analytic review was undertaken using the Comprehensive Meta-Analysis Software. A systematic review of the literature identified 612 articles on IT project success. Of these, 46 articles used a range of constructs in studying IT project success. The meta-analytic review resulted in 24 antecedents of IT project success. The result could be explained by adopting a knowledge management perspective as the antecedents (such as team environment, team process, team integration and social factors) were necessary for the creation, storage and transfer of knowledge in leading to IT project success. Theoretical and practical implications are discussed in relation to understanding the contributions of knowledge management to IT project success.